1999
DOI: 10.1021/bi990948+
|View full text |Cite
|
Sign up to set email alerts
|

State-Dependent Disulfide Cross-Linking in Rhodopsin

Abstract: In previous studies, we developed a new method for detecting tertiary interactions in rhodopsin using split receptors and disulfide cross-linking. Cysteines are engineered into separate fragments of the split opsin, the disulfide bond can be formed between the juxtaposed residues by treatment with Cu(phen)3(2+), and then disulfide cross-links can be detected on the gel by an electrophoretic mobility shift. In this study, we utilized this method to examine the cross-linking reactions between native cysteines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 22 publications
3
42
0
Order By: Relevance
“…Disulfide cross-linking approaches have been used previously to investigate light-induced structural changes in the photoreceptor, rhodopsin (9,(25)(26)(27)(28)(29). However, this is the first study demonstrating the usefulness of a disulfide mapping strategy to investigate activity-dependent structural changes in a hormone-activated GPCR.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Disulfide cross-linking approaches have been used previously to investigate light-induced structural changes in the photoreceptor, rhodopsin (9,(25)(26)(27)(28)(29). However, this is the first study demonstrating the usefulness of a disulfide mapping strategy to investigate activity-dependent structural changes in a hormone-activated GPCR.…”
Section: Discussionmentioning
confidence: 98%
“…To address this issue, we decided to employ Cys substitution mutagenesis followed by disulfide cross-linking of Cys residues that are adjacent to each other in the three-dimensional structure of the receptor. This approach has been used successfully in the past to monitor dynamic changes in a number of different membrane proteins including various bacterial chemoreceptors (21-24) and, more recently, bovine rhodopsin (9,(25)(26)(27)(28)(29).To examine the potential proximity of the cytoplasmic ends of TM III and TM VI, we recently described a cross-linking protocol involving the use of a series of Cys-substituted mutant M 3 muscarinic receptors (30). The observed disulfide crosslinking patterns suggested that the cytoplasmic surface of the M 3 receptor protein is highly dynamic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Disulfides have previously been successfully used to restrict intramolecular mobility and probe conformational change in bacterial chemoreceptors (13,14) and rhodopsin (15), as well as to increase the stability of proteins (16). However, efforts to lock in active conformations with disulfides have been challenging.…”
mentioning
confidence: 99%
“…However, efforts to lock in active conformations with disulfides have been challenging. Rhodopsin has thus far been locked only in the inactive form (15); the bacterial aspartate receptor has been locked in forms with up to 4-fold higher enzymatic activity and 8-fold higher affinity for aspartate (17).…”
mentioning
confidence: 99%